Protein-losing enteropathy after Fontan operation - Yuan, Shi-Min (Progress in Nutrition, 2019)
Protein-losing enteropathy (PLE) is a rare but severe complication of Fontan operation with high mortality and recurrent rates. It often develops 1-9 years after Fontan operation. This disorder often leads to chronic malnutrition, global immune dysfunction and failure to thrive in addition to peripheral edemas. PLE is often associated with increased chronic inflammatory biomarkers, such as C-reactive protein, complement fragments and tumor necrosis factor-α, etc., and decreased acute inflammatory biomarkers, for instance, lymphocytes. Abnormal fecal α1-antitrypsin clearance is the golden diagnostic standard of PLE. The management strategies include medical, surgical and interventional therapies. However, none of the proposed treatment shows a specific efficacy to PLE after Fontan operation. Management of choice for PLE relies on the substantial response of the patient to the underlying regimen, and the patients may eventually warrant heart transplantation. The PLE-related mortality is high with cardiac dysfunction, severe infection and multiorgan failure being the major causes of death. Attempts to diminish Fontan failure and seek for effective therapeutic regimen for PLE after Fontan operation are research works of next step.